Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing 2016
DOI: 10.18653/v1/d16-1108
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Language of Online Communities and its Relation to Community Reception

Abstract: This work investigates style and topic aspects of language in online communities: looking at both utility as an identifier of the community and correlation with community reception of content. Style is characterized using a hybrid word and part-of-speech tag n-gram language model, while topic is represented using Latent Dirichlet Allocation. Experiments with several Reddit forums show that style is a better indicator of community identity than topic, even for communities organized around specific topics. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 14 publications
4
26
0
Order By: Relevance
“…This is analogous with previous work on computational sociolinguistics, where researchers have demonstrated that online discussion forums create community norms about language usage, and members adapt their language to conform to those norms (Nguyen et al, 2016). Especially on Reddit, language style is an essential indicator of community identity (Tran and Ostendorf, 2016;Chancellor et al, 2018). Our schemas help us make similar observations, showing that dominant user posting styles in each subreddit seem to be ones that conform to subreddit descriptions.…”
Section: Discussionsupporting
confidence: 77%
“…This is analogous with previous work on computational sociolinguistics, where researchers have demonstrated that online discussion forums create community norms about language usage, and members adapt their language to conform to those norms (Nguyen et al, 2016). Especially on Reddit, language style is an essential indicator of community identity (Tran and Ostendorf, 2016;Chancellor et al, 2018). Our schemas help us make similar observations, showing that dominant user posting styles in each subreddit seem to be ones that conform to subreddit descriptions.…”
Section: Discussionsupporting
confidence: 77%
“…Dansih et al show that a comment's timing relative to the post matter in eliciting responses in the community r/IAmA [5]. Lakkaraju et al/ [6] and Tran et al [7] show that reddit post titles and timing are important factors in the popularity of a post. However, this popularity can be delayed.…”
Section: Related Workmentioning
confidence: 99%
“…Further, Reddit is a widely used platform, ranking 6th in global popularity according to alexa.com in 2018. Reddit has also been shown useful in other prediction tasks, such as ranking popular comments in discussions [6] and general popularity studies [4,11,25].…”
Section: Datamentioning
confidence: 99%